To lose a battle : France 1940 - by Alistair Horne. (Litlle, Brown and Co.)
Third volume in a trilogy; the 1st of which is The fall of Paris; the siege and the Commune, 1870-71; and the 2d of which is The price of glory; Verdun 1916. Bibliography: p. [601]-606.